1988
DOI: 10.1098/rsta.1988.0083
|View full text |Cite
|
Sign up to set email alerts
|

Tectonics and evolution of the central sector of the Himalaya

Abstract: Following the India-Asia collision, intracrustal movements along the Main Central Thrust (MCT) and Main Boundary Thrust (MBT) in a piggy-back-style, thrust duplexes developed that uplifted the Vaikrita (Central) crystallines of the basement to more than 8000 m elevation. Blocking of subduction on the suture and slowing down of movement on the MCT led to the formation of the Trans-Himadri (Malari) Thrust between the Vaikrita basement and the Tethyan cover sediments, and to gravity-induced backfolds and backthru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(33 citation statements)
references
References 21 publications
1
32
0
Order By: Relevance
“…The higher value of radon in water sample #W 9 (160.1 Bq/l) is possibly due to the continued movement along the different shear planes, exhibiting extreme shearing and mylonitization. 29) Radon concentration in groundwater was measured from the joint/fault related and colluvial related springs. The higher radon values (121 Bq/l to 160 Bq/l) were recorded in joint/ fault related springs.…”
Section: Resultsmentioning
confidence: 99%
“…The higher value of radon in water sample #W 9 (160.1 Bq/l) is possibly due to the continued movement along the different shear planes, exhibiting extreme shearing and mylonitization. 29) Radon concentration in groundwater was measured from the joint/fault related and colluvial related springs. The higher radon values (121 Bq/l to 160 Bq/l) were recorded in joint/ fault related springs.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study area of the outer Kumaun Lesser Himalaya, the geomorphic expressions of neotectonics are observed along the SAT, Garampani Fault (GF) and E-W trending system of Fig. 1 Geological map of the study area (Valdiya 1980(Valdiya , 1988b faults, e.g. the Amel and Betalghat-Basgaon Faults (Fig.…”
Section: Introductionmentioning
confidence: 96%
“…It shows intercontinental faults and rejuvenated topography (Valdiya 1993(Valdiya , 2005. A number of NNW-SSE trending right lateral tear faults have been recognized (Middlemiss 1890a, b;Gansser 1964;Valdiya 1976Valdiya , 1988b in the Kumaun Himalaya. The Himalaya is cut across by an extensively active fault system that extends from the Karakoram Fault to the Bengal Plain producing landforms pertaining to active faults (Nakata et al 1984;Nakata and Kumahara 2002).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several studies have shown that the structural grains of Peninsula India extend up to the Lesser Himalaya (Auden, 1935;Valdiya, 1976Valdiya, , 1988Raiverman, 2002). Indeed, the pre-existing crosslineaments within the ophiolites of the Indus-Tsangpo Suture Zone of southern Tibet showing same concept are carried into the higher and Tethyan Himalaya, and up to trans-Himalaya (Gansser, 1980) .The Suru lineament, a major north-south Trans-Asiatic lineament, extends from the Punjab plains in India to the arctic Ocean, running close to the 60 o E meridian, and has been divided into eight segments (see : Raiverman, 1992 (Raiverman, 1992, fig.4) shows their continuity with those in the Eurasian block, as revealed in the spatial distribution pattern of the orographic axes of Eurasia ( Figure 3).…”
Section: Structurementioning
confidence: 99%